Pengaruh Kemudahan dan Keamanan Terhadap Kepuasaan Layanan Moble Banking Bank Sumsel Babel Syariah: ( Studi pada Mahasiswa Fakultas Ekonomi dan Bisnis Islam ) - Serli Serli; Hilaliyah Hilaliyah; Lidia Desiana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study analyzes the influence of ease of use and security on customer satisfaction with the mobile banking services of Bank Sumsel Babel Syariah, particularly among students of the Faculty of Islamic Economics and Business at UIN Raden Fatah Palembang. Using a quantitative approach, data were collected through questionnaires from 100 respondents. The results indicate that ease of use does not have a significant effect, while security has a positive and significant impact. Collectively, ease of use, security, and trust contribute 78.5% to customer satisfaction variability. The study recommends enhancing security systems and usability of the mobile banking application, as well as educating customers on safe usage practices.